PENGARUH TATA KELOLA RISIKO TERHADAP KINERJA PERUSAHAAN PERBANKAN - Faisal Faisal; Novi Inggardiayu Dyah Ismoyorini (Jurnal Penelitian Ekonomi dan Bisnis, 2019)
This study examines the effect of risk governance on bank performance of Indonesian public companies. The sample consists of 86 banking companies listed on Indonesian Stock Exchange for period 2016-2017. The accounting-based and market-based approach were used to measure the performance, while risk governance disclosure was measured by risk disclosure, number of risk committee and frequency of risk committee meetings. The results of this study find that the extent of of risk disclosure and the number of risk committee have significantly effect both on accounting-based and market-based performance. However, this study failed to suggest that the frequency of risk committee meetings affect bank performance. The findings of this study suggest that the presence of good risk governance mechanism may reduce the potential risks faced by banking companies while providing a positive impact on the performance.